Frequency of Depression in Caregivers of Patients with Epilepsy - Amjad Hussain Balouch, Shanza Nazir, Shoaib Ahmed Magsi, Ratan Kumar, Inayatullah Awan, Arjan Kumar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Epilepsy is the neurological issue and disorder that causes fits or seizures, which are brief bursts of involuntary autonomic function or sensation caused by an excessive electrical discharge in the brain. Caregiving of such patient is a difficult experience that can have a negative impact on the caregiver’s physical and mental health. Objective: To determine the frequency of depression in caregivers of patients with epilepsy Study Setting: Department of Psychiatry, Jinnah Hospital Lahore. Duration of Study: May 30, 2017 to November 29, 2017 Study Design: Cross-Sectional Study Subjects & Methods: A total of 130 caregivers of patients with epilepsy were enrolled. Hospital Anxiety Depression Scale (HADS) was use to determine the depression in caregivers of epilepsy patients who were initially non-psychiatric patients,and the cut - off point of 8 or more above in depressive subscale indicated depression. Respondents with score of 8 and above in HADS depression sub-scale was considered to have depression. Data were entered and analyzed using SPSS v22.0. Results: A total of 130caregivers of patients with epilepsy were included. Age range in this study was from 20 to 50years with mean age of 34.5±8.7years. Among 130caregivers of patients with epilepsy, 87(66.9%) were males and 43(33.1%) were females.Among caregivers of patients with epilepsy, 68(52.3%) had depression. Conclusion: Caregivers presented with high depression esteems as they didn’t have a top-quality of life.